2013
DOI: 10.4161/onci.24270
|View full text |Cite|
|
Sign up to set email alerts
|

The novel cancer-testis antigen A-kinase anchor protein 4 (AKAP4) is a potential target for immunotherapy of ovarian serous carcinoma

Abstract: Ovarian cancer is one of the neoplasms affecting the reproductive tract associated with high mortality rate because of limited therapeutic options and an elevated incidence of chemoresistance and recurrence. In this context, immunotherapy may constitute a promising approach to improve survival rates and clinical outcome, raising the need for specific target antigens. Cancer-testis antigens (CTAs) are considered promising candidates in this sense because they are aberrant expressed by various malignancies but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 25 publications
(43 reference statements)
0
34
0
Order By: Relevance
“…Further, our data indicated that majority of CRC patients (84%, 168 of 200) demonstrated AKAP4 expression irrespective of stages and grades suggesting a possible role of AKAP4 in CRC. We have shown earlier that AKAP4 has been documented to be upregulated in breast cancer patients (85%), 12 epithelial ovarian carcinoma (EOC) patients (89%), 13 and cervix cancer patients (86%). 14 Moreover, other laboratories have also confirmed AKAP4 protein expression in 65% prostate cancer patients, 16 25% NSCLC patients, 17 and 42% multiple myeloma patients.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Further, our data indicated that majority of CRC patients (84%, 168 of 200) demonstrated AKAP4 expression irrespective of stages and grades suggesting a possible role of AKAP4 in CRC. We have shown earlier that AKAP4 has been documented to be upregulated in breast cancer patients (85%), 12 epithelial ovarian carcinoma (EOC) patients (89%), 13 and cervix cancer patients (86%). 14 Moreover, other laboratories have also confirmed AKAP4 protein expression in 65% prostate cancer patients, 16 25% NSCLC patients, 17 and 42% multiple myeloma patients.…”
Section: Discussionmentioning
confidence: 98%
“…The RNA was reverse transcribed using a set of primers and High-Capacity cDNA Reverse Transcription Kit (Applied Biosystems, Carlsbad, CA) as described earlier. 13 Following AKAP4 specific primers were used: AKAP4 Forward primer 5 0 -TGATACTACAAT-GATGTCTGATGAT-3 0 , AKAP4 Reverse primer 5 0 -GGAAC-TAGCAGCATCCTTGTAATCTTTATC-3 0 , b-actin was used as an internal control to check the quality of cDNA synthesis with following primers: b-actin Forward primer 5 0 -ATCTGGCAC-CACACCTTCTACAATGAGCTGCG-3 0 , b-actin Reverse primer 5 0 -CGTCATACTCCTGCTTGCTGATCCACATCTGC-3 0 . The PCR products were electrophoresed on 2% agarose gel and photographed under UV light in EC3 Imaging System (UVP, Upland, CA).…”
Section: Rt-pcrmentioning
confidence: 99%
See 2 more Smart Citations
“…Its expression triggers humoral immune responses in ovarian cancer and is associated with malignant properties of cervical, breast and prostate cancer [138]. AKAP4 is currently analyzed as a potential target for cervical cancer immunotherapy [139,140]. The strong expression of AKAP4 in multiple myeloma led to its classification as cancer testes antigen [137].…”
Section: Akaps In Cancermentioning
confidence: 99%